Active Earth:: Rain-induced Landslides in the Canadian Cordillera, July 1988 - Evans, S.; Clague, J. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1989)
Abstract Rain-induced landslides are a major geological hazard in the Canadian Cordillera that impact directly on the economic infrastructure of the region. In July 1988, heavy rains triggered debris flows and related sediment-water flow processes which severed the Alaska Highway in three areas: Muncho Lake, BC, Rancheria, Yukon, and Kluane Lake, Yukon. The events paralysed travel in the region for several days. In addition, the heavy rainfall caused wide spread landsliding over a large area of the northern Cordillera. One of the largest events was acomplex failure at Nahanni Butte, NWT Debris flows originating in the steep watersheds of the Sentinel Range of the RockyMountains severed the highway at six locations in the vicinity of Muncho Lake. At Kluane Lake, the highway was severed innumerous places by debris flows and related processes and at one location, near theSlims River, a debris flow covered over 500 m of highway. A large landslide, covering nearly 2 km2, threatened a National Parkranger station near Nahanni Butte. North-east of the station a large mobile mudflow travelled almost 2 km to the Liard River. The direct cost of restoring the Alaska Highway was in the order of $1.8 M. The paper points to the vulnerability of transportation facilities in mountainous terrain where the location ofroutes necessarily involves the traversing of active geomorphic surfaces.